THYROID CANCER: THE IMPORTANCE OF MOLECULAR-GENETIC EXAMINATION - Malikov Muzaffar Abduvakhobovich (Web of Journals Publishing, 2026)
This article examines the significance of molecular-genetic analysis in thyroid cancer diagnosis and management. Molecular-genetic testing allows for the identification of specific mutations, prediction of tumor behavior, assessment of prognosis, and selection of personalized treatment strategies, including targeted therapy. Early detection of genetic alterations can improve treatment outcomes and reduce the risk of recurrence.
Keywords: Thyroid cancer, molecular-genetic analysis, mutations, prognosis, personalized treatment, targeted therapy.